2020
DOI: 10.3390/molecules25133072
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Micro-Scale Extraction of Bioactive Phenolic Compounds from Vitis vinifera Leaves with Ionic Liquid-Based Surfactants

Abstract: This paper proposes a new sustainable and simple strategy for the micro-scale extraction of phenolic compounds from grapevine leaves with analytical purpose. The method is based on a microwave-assisted solid-liquid extraction approach (MA-SLE), using an aqueous solution of an ionic liquid (IL)-based surfactant as extraction phase. The method does not require organic solvents, nor any clean-up step, apart from filtration prior to the injection in the analytical system. Two IL-based surfactants were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Considering the promising results obtained in our previous study related to the extraction of phenolic compounds from Vitis vinifera leaves by an IL-MA-SLE method using [C 16 C 4 Im + ][Br – ][ 20 ], this IL was selected to optimize the extraction procedure in the current study. Ultimately, the purpose was to use this IL as a screening solvent but intending the further use of ILs with lower toxicity and higher analytical performance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering the promising results obtained in our previous study related to the extraction of phenolic compounds from Vitis vinifera leaves by an IL-MA-SLE method using [C 16 C 4 Im + ][Br – ][ 20 ], this IL was selected to optimize the extraction procedure in the current study. Ultimately, the purpose was to use this IL as a screening solvent but intending the further use of ILs with lower toxicity and higher analytical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method has fewer steps, as shown in Figure S6 of the SM , making the process less tedious and faster due to the elimination of the clean-up step. Our previous study demonstrated that the use of IL-based surfactant aqueous solutions as an extraction solvent avoids the co-extraction of green chlorophylls that could compromise the analytical performance of the chromatographic column [ 20 ]. In the current study, the entire IL-MA-SLE consumes less time, 15 min compared to the 45 min required in the UA-SLE method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations